Intestinal Pioneer Colonizers as Drivers of Ileal Microbial Composition and Diversity of Broiler Chickens - Rodrigues, Denise R.; Winson, Emily; Wilson, Kim M.; Briggs, Whitney N.; Duff, Audrey F.; Chasser, Kaylin M.; Bielke, Lisa R. (Frontiers in Microbiology, 2020)
Given that recent advances in metagenomics have highlighted the importance of intestinal microbes for poultry health, there has been a corresponding search for early manipulation strategies of intestinal microbiota in order to advance immune system development and optimize functional properties of growth. In this study, we used the in ovo technique as an experimental model to address how early bacterial intestinal colonization could affect the development and establishment of the mature ileal microbiota. Inoculations containing one of the following: 0.2 ml of 0.9% sterile saline (S), approximately 102 cells of Citrobacter freundii (CF), Citrobacter species (C2) or lactic acid bacteria (L) were administered via in ovo into the amnion. Results showed that Enterobacteriaceae abundance was negatively correlated with aging, although its high population at day of hatch affected the microbiota composition, delaying mature microbiota establishment. L treatment increased colonization of butyrate-producing bacteria by three and 10 days, and segmented filamentous bacteria in the lower ileum by 10 days. On the other hand, L-probiotic decreased the population of Enterococcaceae. In addition, L and C2 microbial communities were less diverse at 10 days than at three days in the upper ileum. Importantly, these findings provide a valuable resource for a potential study model for interactions between microbial colonization and associated immune responses. In conclusion, our analysis demonstrates that intestinal pioneer colonizers play a critical role in driving the course of microbial community composition and diversity over time, in which early-life exposure to L-based probiotic supported selection alongside greater colonization of symbiotic populations in the ileum of young broilers.